Managing Employee Absenteeism - Thekedam, Joseph Sebastian (Ushus Journal of Business Management, 2010)
Employee absence rate, causes of employee absenteeism and the effects of employee absences on productivity are topics of discussion in many organizations. One reason is that high rates of employee absence may signal weak management and poor labor-management relations. A second reason is that reducing rates of employee absence may be an effective way to improve productivity. This paper reports the results of a study of employee absences in education, a large, labor-intensive industry. Employee absence in education is a serious problem which adversely affects the curriculum, discipline of the students and academic achievements of the students. In addition to economic loss, teacher absences induces students’ absenteeism and causes damage to the school’s reputation and it may even affect the school’s general existence. This research paper tries to find out employee absenteeism rate, analyse the causes of employee absenteeism and design suitable programmes for encouraging better attendance of employees. Correlation analysis revealed that employee absenteeism was significantly related to demographic variables, cultural factors, personal characteristics of employees, community characteristics and organisational factors.